Assembly and analytical validation of a metagenomic reference catalog of human gut microbiota based on co-barcoding sequencing - Huang, Yufen; Jiang, Puzi; Liang, Zhengjiao; Chen, Rouxi; Yue, Zhen; Xie, Xuefeng; Guan, Changge; Fang, Xiaodong (Frontiers in Microbiology, 2023)
Human gut microbiota is known to have the second largest genome in the human body and is related to human health and disease. The microbiota genome is important for their functions and metabolites, however, accurate genomic access to microbiota of Chinese persons is hindered due to the difficulty of cultivating and the shortcomings of sequencing technology. Therefore, we applied stLFR library construction method to assemble the microbiota genomes and demonstrated that assembly property outperformed standard metagenome sequencing. Based on assembly genomes as a reference, SNPs, INDELs, and HGT gene analysis was performed, and the results demonstrated that there are significant differences in the number of SNPs and INDELs among different individuals, the individual has its own unique species variation spectrum, and the similarity of strains within individuals decreased over time. In addition, the coverage depth analysis of the stLFR method shows that only 60X is sufficient for SNPs calling. HGT analysis showed that genes with functions of replication, recombination and repair, mobilome prophages, transposons were the most transferred genes among different bacterial species in individuals.